ANALISIS PENGARUH LUAS KEBUN, PRODUKSI DAN HARGA EKSPOR CENGKEH TERHADAP VOLUME EKSPOR CENGKEH JAWA TENGAH - Muhammad Hibatul Haqqi Zuhri; Jozef Bambang Tri Joga; Umar Farouk (JOBS (Jurnal Of Business Studies), 2016)
The purpose of this research to analyze relations between variable of the width of field plantation, production and pricing clove exports to the volume of exported cloves from central java .The method of analysis data used in the research is analysis multiple regression .The data used in the research are data time series quarter from year 2006- 2014 ( 9 years ) .The result showed that all three variables, the width of field plantation , production and pricing exports have simultaneously significant impact on the volume of exported cloves from central java.The width of field plantation and production have positive impact and significantly to the volume of exported cloves from central java while the price exports have negative impact and significantly to the volume of exports cloves central java